Penerapan Sistem Absensi Fingerprint Dengan Menggunakan Visual Basic 6.0 di CV. MEDIA INOVASI - Iwan Koerniawan; Denny Setyawan (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2021)
Attendance is an important thing for an agency or company. because it is used in calculating the amount of an employee's salary or wages and from attendance it can also see the discipline of employee attendance. Therefore, in its implementation, the attendance process requires accuracy in its implementation so as not to hinder company performance.This final project is designing an employee attendance system at CV. INNOVATION MEDIA which is useful for providing good attendance information quickly and easily, also through this study is expected to provide convenience to employees of CV. INNOVATION MEDIA in doing attendance. Employee attendance system design at CV. INNOVATION MEDIA was developed using Visual Basic 6.0 software and with Finger Print as a tool. This system records employee attendance in the form of a daily attendance list. It is used to accommodate the data needed to streamline the information system.With this system, it is expected that the data processing process will be more effective and efficient. In searching for data it will be easier. The purpose of this study is to design an employee attendance information system which is expected to help the